2014
DOI: 10.5424/sjar/2014122-4639
|View full text |Cite
|
Sign up to set email alerts
|

Linseed, microalgae or fish oil dietary supplementation affects performance and quality characteristics of light lambs

Abstract: The aim of this work was to improve the fatty acid profile of meat from light lamb, frequently reared in Spain and in other Mediterranean countries. A total of 44 light lambs fed different n-3 polyunsaturated fatty acids sources were studied: control (C) (palm oil), extruded linseed (L), extruded linseed mixed with microalgae (LM) and fish oil (FO). The productive performance from 14.7 to 26.2 kg of live weights and meat quality characteristics during refrigerated storage were assessed. Lambs fed FO showed low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
32
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 36 publications
10
32
1
1
Order By: Relevance
“…A remarkable increase of vaccenic acid, linoleic acid (C18:2 c9 c12), ALA, and the sum of LC-PUFA n-3 was induced by the EL-20-enriched diet. These results are in agreement with data obtained by de la Fuente-Vázquez et al [ 7 ] with Manchego lambs fed a concentrate containing 8.7% EL. In this study a decrease in SFA and MUFA and an increase in PUFA and n-3 FA, C18:3 n-3 in particular (6.5-fold higher compared to control), was observed.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…A remarkable increase of vaccenic acid, linoleic acid (C18:2 c9 c12), ALA, and the sum of LC-PUFA n-3 was induced by the EL-20-enriched diet. These results are in agreement with data obtained by de la Fuente-Vázquez et al [ 7 ] with Manchego lambs fed a concentrate containing 8.7% EL. In this study a decrease in SFA and MUFA and an increase in PUFA and n-3 FA, C18:3 n-3 in particular (6.5-fold higher compared to control), was observed.…”
Section: Resultssupporting
confidence: 93%
“…These results are in accordance with Moloney et al [ 39 ], who reported similar trends in final pH and color of SM and LL of lambs fed with linseed oil and NaOH-treated linseed compared to a control group. Similarly, only few differences were reported in the meat composition of Manchego lambs fed with EL, when compared to control animals, and no effects were recorded in the meat of lambs derived from Churra ewes fed with a linseed oil-enriched diet [ 7 , 40 ]. However, the comparison with data reported by other authors should be carefully considered as the differences between experimental factors can influence the final meat quality characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Carcass fatness was subjectively evaluated using the 1-4 points scoring system following the community scale for classification of lamb carcass [10]. The dorsal fat thickness was measured at 4 cm from the carcass midline and at 4 cm from the caudal edge of the last rib with a digital calibrator [11]. The kidney knob and channel fat (KKCF) score was assessed using a 1 to 3 scale [12].…”
Section: Slaughter Measurements and Samplingmentioning
confidence: 99%
“…Three measurements were made on each location and values were averaged before statistical analysis. The calibration was performed as described by [11] using standard white tiles prior to color measurements. The color coordinates were expressed following the CIELAB system [13] as L* (brightness), a* (red-green index) and b* (yellow-blue index).…”
Section: Slaughter Measurements and Samplingmentioning
confidence: 99%
“…Ponad 6-krotny wzrost zawartości kwasu C18:3 stwierdzili Fuente-Vazquez i wsp. [7] w mięsie jagniąt lokalnej rasy, żywionych do woli mieszanką treściwą z 12,5-procentowym udziałem nasion lnu. Autorzy zaobserwowali także wzrost zawartości innych kwasów z grupy n-3 (C20:5, C22:5, C22:6), co również miało wpływ na znacznie niższy, a więc korzystniejszy stosunek n-6/n-3 w grupie żywionej mieszanką z dodatkiem nasion lnu.…”
Section: Cechy Tuczne I Rzeźneunclassified